2018
DOI: 10.1038/s41598-017-18332-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural ensemble-based docking simulation and biophysical studies discovered new inhibitors of Hsp90 N-terminal domain

Abstract: Heat shock protein 90 (Hsp90) is one of the most abundant cellular proteins and plays a substantial role in the folding of client proteins. The inhibition of Hsp90 has been regarded as an attractive therapeutic strategy for treating cancer because many oncogenic kinases are Hsp90 client proteins. In this study, we report new inhibitors that directly bind to N-terminal ATP-binding pocket of Hsp90. Optimized structure-based virtual screening predicted candidate molecules, which was followed by confirmation using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…To identify a direct protein target of SFX in cancer cells, we applied an in silico approach based on a Similarity Ensemble Approach (SEA), a method developed by our group 29 . Using data from the BindingDB, SEA identified four proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify a direct protein target of SFX in cancer cells, we applied an in silico approach based on a Similarity Ensemble Approach (SEA), a method developed by our group 29 . Using data from the BindingDB, SEA identified four proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such false-positives might be a result of conformational changes in the ChE enzymes upon binding of ligands and the case-dependent performances of docking algorithms in prioritizing true-positives. 61 Further, receptor plasticity also plays a significant role in false-positive docking results. 62 Interestingly, a study conducted by Pahl et al reported that compounds that showed higher docking scores were found to have zero inhibitory action.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the numerous benefits associated with structure-based virtual screening, there are a few drawbacks that may arise such as false-positive results. Kim et al (2018) suggested that these may occur as a result of conformational changes of the receptor through ligand binding and also via docking algorithm preferences in selecting true-positives, which may require evaluation on a case-by-case basis. One way to prevent false positives is to conduct in vitro experiments, as both docking and ADME/T predictions do not warrant efficiency of the compounds.…”
Section: Discussionmentioning
confidence: 99%